Sustainable P-enriched biochar-compost production: harnessing the prospects of maize stover and groundnut husk in Ghana’s Guinea Savanna - Fianko, Daniel A.; Nartey, Eric K.; Abekoe, Mark K.; Adjadeh, Thomas A.; Lawson, Innocent Y. D.; Amoatey, Christiana A.; Sulemana, Nasirudeen; Akumah, Asiwome M.; Baba, Mutala E.; Asuming-Brempong, Stella (Frontiers in Environmental Science, 2023)
Farmers in resource-poor areas of the Guinea Savanna zone of Ghana often face declining soil fertility due to the continuous removal of nutrient-rich harvested produce from their fields. This study focuses on the Lawra Municipality in the Guinea Savanna zone of Ghana, where low soil fertility, specifically, limits phosphorus (P) bioavailability and hinders crop production. The objective of this research is to formulate P-enhanced biochar-compost from maize stover (MS) and groundnut husk, which abound in the area, to close the nutrient loop. MS was co-composted with groundnut husk biochar at varying rates of 0, 10, 20, 30, and 40% by volume. To facilitate decomposition using the windrow system, the composting heaps were inoculated with decomposing cow dung, and the moisture content was kept at 60% throughout the monitoring period. The addition of biochar shortened the lag phase of composting. However, rates above 20% resulted in reduced degradation of MS. Biochar incorporation enriched the available phosphorus content in the final compost from 286.7 mg kg−1 in the non-biochar-compost to 320, 370, 546, and 840.0 mg kg−1 in the 10, 20, 30, and 40% biochar-compost, respectively.